Colaboração criativa em times mediados por plataformas digitais - Terceiro, Luciana Hamamoto (2019)
Work teams are increasingly becoming virtual and their working and collaboration relationships are mediated by digital platforms. In these virtual environments, team members need to develop projects, carry out activities and tasks in a collaborative and ideally creative way in order to achieve better levels of quality and performance. In this scenario of rapid changes and developments, we seek to investigate in this research the hypothesis that teams with professionals working remotely can collaborate creatively in solving problems and challenges, even working and communicating only through digital platforms. The methodological procedure covers literature review and qualitative research to analyze the remote work dynamics mediated by digital collaborative platforms, and aims to understand the dynamics and adequate resources and obstacles to the production of knowledge and creative collaboration in digital teams